2023
DOI: 10.3390/jfb14090469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Macro-Design, -Length, and -Diameter on Primary Implant Stability Depending on Different Bone Qualities Using Standard Drilling Protocols—An In Vitro Analysis

Milan Stoilov,
Ramin Shafaghi,
Helmut Stark
et al.

Abstract: (1) Background: Primary implant stability is vital for successful implant therapy. This study explores the influence of implant shape, length, and diameter on primary stability in different bone qualities. (2) Methods: Three implant systems (two parallel-walled and one tapered) with various lengths and diameters were inserted into polyurethane foam blocks of different densities (35, 25, 15, and 10 PCF) using standard drilling protocols. Primary stability was assessed through insertion torque (IT) and resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…The ISQ value range from 1 to100. A value of ISQ < 60 represents low stability, ≥60 ISQ ≤ 69 represents medium stability and ISQ ≥ 70 high stability [16,18]. According to our results, there was a progressive increase in IT and ISQ over time, regardless of the technique used, SD or OD.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The ISQ value range from 1 to100. A value of ISQ < 60 represents low stability, ≥60 ISQ ≤ 69 represents medium stability and ISQ ≥ 70 high stability [16,18]. According to our results, there was a progressive increase in IT and ISQ over time, regardless of the technique used, SD or OD.…”
Section: Discussionsupporting
confidence: 54%
“…The IT, initially developed by Johansson and Strid, is applied with a torque wrench, and is the measure of the frictional resistance obtained at the time of implant placement [17,18]. The maximum value of the insertion torque was recorded in Newton centimeter (Ncm) [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Comuzzi et al compared polyurethane blocks of different densities and reported that implant insertion and removal torques increased with increasing density [ 43 ]. Similarly, Stoilov et al found that polyurethane blocks used in relation to different densities affected the ITs of the implants, with higher ITs being achieved with higher densities [ 44 ]. According to these studies, the use of polyurethane blocks for comparison between the ITs obtained from different sockets is considered appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical and behavioral factors of stress (amplitude, direction, rate, and frequency) affect bone remodeling, particularly in the neck region (Cehreli et al, 2004). Thus, cylindrical implants may require a higher insertion torque to achieve primary stability, and if exceeded by 50 Ncm may potentiate MBL (Nandini, et al, 2022;Stoilov, et al, 2023). , demonstrated that cylindrical implants showed a slight increase in MBL compared to conical implants, but not in a statistically significant way.…”
Section: Discussionmentioning
confidence: 99%